Making Payments More Efficient for the Philippines Conditional Cash Transfer Program - Acosta, Pablo; Endo, Isaku; Garcia Garcia Luna, Jose Antonio; de Guzman, Aisha; Okamura, Yuko (World Bank, Washington, DC, 2019)
The Pantawid Pamilyang Pilipino Program (Pantawid Pamilya) has rapidly expanded to become the largest social protection and human development program in the Philippines. Over the last decade, the evolution of the Pantawid Pamilya was not only about its size and coverage, but also related to the program design and the quality of implementation. Payment is one of key elements which improved over time; however, severe challenges that hamper their efficiency remain unaddressed. For instance, the 4Ps has not taken full advantage of the existing payment system in the Philippines yet. The Pantawid Pamilya has great potential to increase the use of electronic payments, which significantly saves time and removes paperbased documentation. Thus, this note recommends the Government of the Philippines to develop a strategic payment reform agenda, under which 4Ps should allow beneficiaries to receive payments at any transaction account of their choice. In parallel, it is key to revisit business processes and invest in the management information system to reduce manual transactions to achieve more efficient payment. Beyond efficiency, the Pantawid Pamilya program can also strategically leverage different financial modalities/service providers to promote the financial inclusion agenda for beneficiaries. While service providers currently see the Pantawid Pamilya payout as a goodwill rather than a business opportunity, there is great potential for beneficiaries to become the customers of their products and services with a mainstream account.